Factors Influencing the Effectiveness of Electronic Medical Record Implementation: Determinants of Electronic Medical Record Success - Prila Dwi Wahyuningtyas Wahyuningtyas; Chatarina Umbul Wahjuni; Atik Setiawan (Innovative Approaches in Health Science Journal, 2026)
Background: Advances in information technology have brought significant changes to healthcare systems, one of which is through the implementation of Electronic Medical Records. Electronic Medical Records (EMR) are an important component in improving the quality of healthcare services to be effective, efficient, and sustainable. However, the success of its implementation is greatly influenced by various organizational and individual factors. This study aims to analyze the factors that influence the effectiveness of Electronic Medical Record usage at Dungus Regional General Hospital. Method : This study used a quantitative approach with a cross-sectional design. Data collection was conducted using a structured questionnaire administered to 143 respondents consisting of doctors, nurses, medical record staff, and other health workers using proportional random sampling. The independent variables included perceived usefulness, perceived ease of use, management support, training attended, and availability of supporting infrastructure. The dependent variable was the use of EMR. Data analysis was perfoEMRd using descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression tests. Results: The results show that management support is the most dominant factor influencing the effectiveness of EMR use (p = 0.031), followed by perceived ease of use (p = 0.039), perceived usefulness (p = 0.044), training attended (p = 0.044), and availability of supporting infrastructure (p = 0.044). The coefficient of determination (R²) value of 0.621 indicates that 61.7% of the effectiveness of EMR use can be explained by these five variables. This means that the effectiveness of EMR use at Dungus Regional General Hospital is significantly influenced by individual, organizational, and technological factors. Conclusion: This study concludes that perceived usefulness, perceived ease of use, management support, training, and supporting infrastructure significantly and jointly influence EMR effectiveness at Dungus Hospital (R² = 0.621; p = 0.000), with management support emerging as the most dominant factor in ensuring effective, optimal, and sustainable EMR implementation.